Structural and optical properties of Sn doped ZnO-rGO nanostructures using hydrothermal technique. (2020) - Priyadharsan, A.; Shanavas, S.; Vidya, C.; Kalyana Sundar, J.; Acevedo, R.; Anbarasan, P.M.
Abstract: The structural and the optoelectronic properties of reduced graphene oxide based nanostructures were manageable, creating them favourable for applications in miscellaneous electronic devices. In this present work, Tin doped Zinc oxide/reduced graphene oxide (Sn doped ZnO/rGO) nanostructures were synthesized using a hydrothermal-assisted self-assemble method, and their structural and optical studies were investigated. The microstructural results confirmed the successful decoration of Sn-doped ZnO/rGO nanostructures. Therefore, these results can promote an excellent candidate for the applications of environmental issues.